Pembuatan dan Pelatihan Website Potensi Dusun kepada Perangkat Desa Bancong Kabupaten Madiun - Anardani, Sri; Rozak, Muhamad Arif Fatkhur; Ahsan, Muhammad Salimy; Foret, Foret; Sari, Dwi Novita; Meliana, Susan (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
Villages are the starting point for national development to improve the quality of life of the community. Advances in information technology can have a positive impact on villages, one of which is helping improve the quality of life of village communities through access to website information. Bancong Village is a village located in the Wonoasri District, Madiun Regency. Over time, Bancong Village has established an Instagram social media account as a means of informing about the village's potential and promoting it. However, social media usage is not optimal due to infrequent postings and a lack of information related to the potential of each hamlet. Bancong Village does not yet have a website that serves as an information platform and accommodates all hamlet information from Bancong Village. The solution offered in this community service activity is the creation and training of a village website. The activity method is implemented through three stages: an introduction consisting of a survey and interviews, then the implementation of website creation and training, and the final stage is evaluation. The evaluation stage found that 80% of training participants were able to operate the village website features independently.